Experiences of typically developing siblings of children with profound intellectual and multiple disabilities during the COVID-19 pandemic in Poland. - Niedbalski, Jakub (International Journal of Developmental Disabilities, 2026)
Objectives: This study aims to provide insight into the experiences of minor siblings of people with profound intellectual and multiple disabilities during the COVID-19 pandemic. Methods: The research was based on information obtained from typically developing siblings of persons with profound intellectual and multiple disabilities. A total of 16 people were enrolled in the study. They were interviewed face-to-face from June to October, 2022. Analysis relied on open and axial coding performed by means of grounded theory methodology procedures. Results: For the purpose of this study, the pandemic experiences cited by the siblings of people with profound intellectual and multiple disabilities were classified into several key domains: additional strain, feeling of frustration, reinforcement of relationship, further familiarization with sibling, sense of injustice, greater sympathy for parents, feeling of loneliness, gaining more confidence in one's own capabilities, sense of maturity. Conclusions: Siblings of people with profound intellectual and multiple disabilities recalled both positive and negative experiences during the COVID-19 pandemic, pointing out areas and facets of their lives and social relationships that either showed improvement or deterioration in their view.